A Study of the Conditions of the Iraqi Provinces from 1876 to 1908: A Historical Study - Dr. Fahd Owaid Abd Al-Baiji (Journal of College of Education, 2025)
This study examines the transformative changes that occurred in the Iraqi provinces during the latter half of the 19th century. This period followed a long era of neglect and decline in all areas. The reforms significantly impacted political, economic, cultural, and social life, laying the groundwork for the future Iraqi state. The study is divided into three sections, detailing public life in the Iraqi provinces from 1876, when the Ottoman Constitution was established, to 1908, the year of the coup that brought the Unionists to power, marking a distinct period in Iraqi history.